On one application of Fourier analysis in plastic surgery - Rakhimov, Abdumalik A.; Zainuddin, Hishamuddin (World Science Publishing Company, 2011)
In present paper, we discuss the spectral methods of measurement of the degree of speech and/or quality of sound by comparing the coefficient of performance indicators depending on energy distributions, ratio of energy of the fundamental tone and energy of overtones. Such a method is very efficient for string oscillation with different initial conditions and it is useful for justification of applications of Fourier analysis in plastic surgery in treatment of some medical diseases.